2001
DOI: 10.1007/bf03190319
|View full text |Cite
|
Sign up to set email alerts
|

Automated examination notification of Emergency Department images in a picture archiving and communication system

Abstract: This study compares the timeliness of radiology interpretation of Emergency Department (ED) imaging examinations in a picture archiving and communication system (PACS) before and after implementation of an automated paging system for notification of image availability. An alphanumeric pager for each radiology subspecialty (chest, pediatrics, bone, neuroradiology, and body) was used to alert the responsible radiologist that an ED imaging examination is available to be viewed on the PACS. The paging system was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Our results are in agreement with those of a study in which implementation in an emergency department of a similar automated paging system for notification of image availability provided more timely reporting and less lost cases without a report (8).…”
Section: Pager Notification and Report Verification Timessupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with those of a study in which implementation in an emergency department of a similar automated paging system for notification of image availability provided more timely reporting and less lost cases without a report (8).…”
Section: Pager Notification and Report Verification Timessupporting
confidence: 92%
“…In addition to improving communication between physicians by producing an official report more rapidly, a reduction in turnaround times can also produce increased revenue because of the fewer days during which charges are in accounts receivable (1)(2)(3)(4)(5)(6)(7)(8). Report turnaround times are also one of the standards regulated by the American College of Radiology (Standard for Communication-Diagnostic Radiology), accreditation organizations, utilization review panels, and some managed care organizations.…”
mentioning
confidence: 99%
“…These technologies included pager-notification systems [135][136][137], digital imaging [138], computer coded reporting [139], workflow management system [140]. Two studies used the controlled postintervention design [138,139] while the remaining studies used the uncontrolled pre-and post-intervention designs [135][136][137]140].…”
Section: Other Technologiesmentioning
confidence: 99%
“…All five studies measured the RTAT with different timelines and included different patient population as well. Most of the studies reported positive findings [135-137, 139, 140], however one study noted that the gains were not sustained beyond 1 week post implementation of a pager-notification system [136,137]. Mixed results were reported on a digital radiography system [138].…”
Section: Other Technologiesmentioning
confidence: 99%
See 1 more Smart Citation